Biallelic mutations of CFAP58 are associated with multiple morphological abnormalities of the sperm flagella. Issue 3 (18th December 2020) - Sha, Yankun; Sha, Yanwei; Liu, Wensheng; Zhu, Xingshen; Weng, Mingxiang; Zhang, Xinzong; Wang, Yifeng; Zhou, Huiliang
Abstract: Multiple morphological abnormalities of the sperm flagella (MMAF) is a severe type of teratozoospermia. In this study, whole‐exome sequencing was conducted on 55 patients with MMAF, and biallelic mutations of CFAP58 were identified in two patients. The variants are rare and pathogenic, and CFAP58 was absent in the CFAP58‐ mutated sperm. The F037/II:1 couple benefited from intracytoplasmic sperm injection (ICSI). This study further indicated that CFAP58 is a pathogenic gene associated with MMAF and ICSI is an effective treatment. Abstract : The multiple morphological abnormalities of the sperm flagella (MMAF) is one of the most severe types of teratozoospermia. In this study, we conducted whole‐exome sequencing on 55 MMAF patients to identify the genetic etiology. Biallelic mutations of CFAP58 were identified from two patients. The variants are rare and disease causing, and CFAP58 was absent in the patients' sperm. Moreover, the TEM results showed the absence of central pairs and disruption of the DMTs. Intracytoplasmic sperm injection (ICSI) was carried out for couple of F037/II:1, his wife became pregnant and gave birth to a baby. This study further demonstrates that CFAP58 is a pathogenic gene of MMAF.